Standards compliance in industrial agents applications - Seixas, Inês Cristina Vinhas (2014)
Multi-agent systems are a suitable approach to address the current requirements imposed to companies demanding for more flexible, adaptive and reconfigurable systems. In spite of the promising perspective, only a reduced number of such solutions are running in industrial scenarios. Standardization is recognized as a major issue in the development of devices, systems or processes in industrial environments, constituting a real road-blocker for the wider acceptance of agent-based solutions in industry. This paper discusses the importance of standardization compliance in the development of industrial agent-based solutions and the actions to be performed to overcome this issue.